Impact of regular cystoscopy on prognosis in non–muscle-invasive bladder cancer: A nationwide study - Jeong-Soo Kim; Jooyoung Lee; Chung Un Lee; Tuan Thanh Nguyen; Se Young Choi (Investigative and Clinical Urology)
Purpose: Transurethral resection of bladder tumors (TUR-BT) requires follow-up evaluation by cystoscopy. We sought to evaluate the prognosis of non–muscle-invasive bladder cancer (NMIBC) patients within 6 months of surgery to identify the optimal timing for the first cystoscopy after TUR-BT. Materials and Methods: In this retrospective analysis, patients newly diagnosed with NMIBC were divided into two groups according to whether they underwent cystoscopy within 6 months after TUR-BT. We considered four outcomes: recurrence, progression, cancer-specific mortality, and all-cause mortality. Inverse probability treatment weighting (IPTW)-adjusted Kaplan–Meier analysis was performed to identify the difference in survival for each outcome stratified by cystoscopy status within 6 months after the first TUR-BT. We employed Cox regression models with IPTW to estimate the hazard ratios (HRs) of each outcome according to cystoscopy status. Results: Among 40,678 patients, 11,940 (29.4%) did not undergo cystoscopy within 6 months. The risk of recurrence was higher for patients who underwent cystoscopy than those who did not (HR 1.32, 95% confidence interval [CI] 1.26–1.38, p<0.001). By contrast, the cystoscopy group had a lower risk of progression compared to the non-cystoscopy group (HR 0.70, 95% CI 0.65–0.76, p<0.001), with lower cancer-specific mortality (HR 0.62, 95% CI 0.56–0.68, p<0.001) and all-cause mortality (HR 0.58, 95% CI 0.56–0.60, p<0.001). Conclusions: Cystoscopy within 6 months was associated with a higher risk of recurrence but a lower risk of progression and death. Therefore, regular cystoscopy after the first TUR-BT for NMIBC is essential to ensure favorable survival outcomes.